Evaluating the Managerial Behavior of Managing Knowledge in Chinese SMEs - Liu, Yao; Abdalla, Ahmed N. (Springer US, 2013)
Recently, the evaluation of knowledge management has become increasingly significant. Nevertheless, few relevant studies explicitly distinguished knowledge management performance from knowledge management effectiveness. This paper covers both sides and introduces a new knowledge management measurement index. It establishes a comprehensive evaluation model by measuring three stages of knowledge management behavior: environmental analysis, knowledge management activity planning, and knowledge management implementation decision making. Data were collected through questionnaires from 100 small and medium sized enterprises in China. The statistical results show that the three stages positively and significantly contribute to the index. The environmental analysis influences most, with the knowledge management activity planning less and the knowledge management implementation decision making least. Finally, it proposes some useful suggestions for enterprises to assess, to predict and to guide their knowledge management practice.